2019
DOI: 10.18235/0001977
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Preferences for Proximity and the Implications for Staffing Schools: Evidence from Peru

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license. Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…This may be due to different levels of labor flexibility for these groups. Such patterns, which have already been documented in the literature (see Bertoni et al 2019), are confirmed in our sample. 20 Given how remote the disadvantaged schools are (approximately four times farther away from the province capital than the rest of the schools), it is plausible that the treatments were not effective among individuals with lower mobility (e.g., those for whom commuting longer distances is more costly), who are more often women.…”
Section: Results and Interpretationsupporting
confidence: 91%
See 3 more Smart Citations
“…This may be due to different levels of labor flexibility for these groups. Such patterns, which have already been documented in the literature (see Bertoni et al 2019), are confirmed in our sample. 20 Given how remote the disadvantaged schools are (approximately four times farther away from the province capital than the rest of the schools), it is plausible that the treatments were not effective among individuals with lower mobility (e.g., those for whom commuting longer distances is more costly), who are more often women.…”
Section: Results and Interpretationsupporting
confidence: 91%
“…In this regard, Table 1 shows that out of the 12,300 public schools that had vacancies in the 24 regions of Peru in 2019, 6,424 (52%) were not selected by any candidate at the national stage. The difference in terms of observable characteristics between these two groups of schools is striking and illustrates teacher preferences for more advantaged institutions: those not selected are notably more rural, farther from the province capital, with less access to basic services, and with a greater proportion of low-performing students (these preferences are consistent with the findings in other papers; see, for instance, Bertoni et al 2019).…”
Section: Disadvantaged Schools and The External Rewards Schemesupporting
confidence: 84%
See 2 more Smart Citations
“…Subject competency test have shown to correlate with teacher value added and other dimensions of teacher quality in several contexts (Bold et al, 2017;Estrada, 2019;Gallegos et al, 2019;Araujo et al, 2020). In Perú in particular, Bertoni et al (2021) document strong correlations between various measures of teaching effectiveness and the score in the curricular and pedagogical knowledge module of the evaluation test. Competent teachers are defined in Figure 1 as those who attain a score of at least 60% in that module of the test.…”
Section: Inequality Of Education Inputsmentioning
confidence: 97%